Răspuns :
f(1)=a+b
f(1)=1
a+b=1
f(-3)=-3a+b
f(-3)=-7
-3a+b=-7
a+b=1⇒a=1-b
-3a+b=-7
-3(1-b)+b=-7
-3+3b+b=-7
4b=-7+3
4b=-4
b=-4:4
b=-1
a=1-b
a=1-(-1)
a=1+1
a=2
f(1)=1
a+b=1
f(-3)=-3a+b
f(-3)=-7
-3a+b=-7
a+b=1⇒a=1-b
-3a+b=-7
-3(1-b)+b=-7
-3+3b+b=-7
4b=-7+3
4b=-4
b=-4:4
b=-1
a=1-b
a=1-(-1)
a=1+1
a=2
[tex]f(1)=1\Leftrightarrow a+b=1\\
f(-3)=-7\Leftrightarrow -3a+b=-7[/tex]
[tex] \left \{ {{a+b=1} \atop {-3a+b=-7}} \right. \Leftrightarrow \left \{ {{b=1-a} \atop {-3a+1-a=-7}} \right. \Leftrightarrow \left \{ {{b=1-a} \atop {-4a=-8}} \right. \Leftrightarrow \left \{ {{b=-1} \atop {a=2}} \right. [/tex]
[tex]f(x)=ax+b=2x-1[/tex]
[tex] \left \{ {{a+b=1} \atop {-3a+b=-7}} \right. \Leftrightarrow \left \{ {{b=1-a} \atop {-3a+1-a=-7}} \right. \Leftrightarrow \left \{ {{b=1-a} \atop {-4a=-8}} \right. \Leftrightarrow \left \{ {{b=-1} \atop {a=2}} \right. [/tex]
[tex]f(x)=ax+b=2x-1[/tex]